PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA GURU DI SMP TAMAN SISWA PEMATANGSIANTAR - Hendrick Sasimtan Putra; Vivi Candra; Debi Eka Putri; Farida Hanum (Universitas Mahendradatta, 2025)
This study aims to analyze the representation of OrganizationalCitizenship Behavior (OCB) and teacher performance at SMP Taman SiswaPematangsiantar, as well as evaluate the influence of OCB on teacherperformance. The research employs a quantitative design with a descriptiveapproach through literature and field studies, involving a population of 24individuals. Data were collected through questionnaires, interviews, anddocumentation, and analyzed using normality tests, descriptive analysis, andquantitative analysis. The results indicate that OCB and teacher performanceare categorized as good. Furthermore, it was found that OCB has a positive andsignificant influence on teacher performance. The relationship between OCBand teacher performance is strong, with OCB making a significant contributionto explaining the teacher performance variable. These findings highlight thestrategic role of OCB in enhancing teacher performance, making theoptimization of OCB a crucial factor in improving the quality of education.